Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1136/heart.85.1.e3
|View full text |Cite
|
Sign up to set email alerts
|

ST segment elevation in the right precordial leads following administration of class Ic antiarrhythmic drugs

Abstract: Electrocardiographic changes were evaluated retrospectively in five patients without previous episodes of syncope or ventricular fibrillation who developed abnormal ST segment elevation mimicking the Brugada syndrome in leads V1-V3 after the administration of class Ic antiarrhythmic drugs. Pilsicainide (four patients) or flecainide (one patient) were administered orally for the treatment of symptomatic paroxysmal atrial fibrillation or premature atrial contractions. The QRS duration, QTc, and JT intervals on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Class IA or IC drugs reportedly are useful for risk stratification of Brugada syndrome by manifesting precordial ST elevation 6 . However, some patients have not experienced episodes of syncope or ventricular fibrillation even though these drugs induced abnormal ST elevation in the patients 7,8 . Thus, the diagnosis of Brugada syndrome may be difficult, particularly in patients in whom ST elevation is not initially apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Class IA or IC drugs reportedly are useful for risk stratification of Brugada syndrome by manifesting precordial ST elevation 6 . However, some patients have not experienced episodes of syncope or ventricular fibrillation even though these drugs induced abnormal ST elevation in the patients 7,8 . Thus, the diagnosis of Brugada syndrome may be difficult, particularly in patients in whom ST elevation is not initially apparent.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 ST elevation with flecainide use can in fact be associated with a Brugada like pattern as in our case. 3,4 Previous studies have suggested that flecainide can induce a new Brugada ECG pattern or can unmask a Brugada syndrome by inducing a type 1 Brugada pattern in patients with pre-existing type 2 or type 3 Brugada patterns. 3e5 Druginduced Brugada pattern can be generally seen at standard therapeutic dose of flecainide and such patients may have a possible underlying genetic predisposition (like SCN5A mutations) causing abnormality of native sodium channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, administration of a sodium channel blocker and changes in autonomic balance may unmask the ECG pattern. Intravenous ajmaline, flecainide or procainamide accentuate ST segment elevation, while beta-adrenergic stimulation normalizes the ECG (3,7,8,10,11).…”
Section: Discussionmentioning
confidence: 99%